2021
DOI: 10.1021/acs.analchem.1c01457
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Polarization of Perovskite-Based Heterostructures via In Situ Semiconductor Generation and Enzyme Catalysis for Signal-Switchable Photoelectrochemical Biosensing

Abstract: Polarization of photoactive materials in current photoelectric (PE) systems is difficult to be adjusted, and thus electron-transfer routes of these systems are unchangeable, which limits their performance in photoelectrochemical (PEC) analysis. Herein, we attempted to modulate the polarization of perovskitebased heterostructures by both in situ semiconductor generation and enzyme catalysis. Owing to their band alignments, Cs 3 Bi 2 Br 9 quantum dots (QDs) and BiOBr are confirmed to construct a Zscheme structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…6−8 Furthermore, lower background signal and higher selectivity show tremendous potential in life analysis. 9,10 For the high-performance PEC assays, photoactive materials are essential, which usually include semiconductor quantum dots (e.g., CdSe), 11 metal−organic frameworks (e.g., PCN-224), 12 perovskite (e.g., CsPbBr 3 ), 13 and organic compounds (e.g., porphyrin). 14 Impressively, porphyrin and its derivatives have high molar absorptivity and rich functional groups, which usually work as high-quality photosensitizers in construction of PEC biosensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6−8 Furthermore, lower background signal and higher selectivity show tremendous potential in life analysis. 9,10 For the high-performance PEC assays, photoactive materials are essential, which usually include semiconductor quantum dots (e.g., CdSe), 11 metal−organic frameworks (e.g., PCN-224), 12 perovskite (e.g., CsPbBr 3 ), 13 and organic compounds (e.g., porphyrin). 14 Impressively, porphyrin and its derivatives have high molar absorptivity and rich functional groups, which usually work as high-quality photosensitizers in construction of PEC biosensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photo-assisted biofuel cells (PBFCs) are a class of photoelectric conversation technology that uses the integration of photoelectrochemistry (PEC) and biofuel cells (BFCs). They have attracted extensive attention and have been widely applied in analysis and energy . Notably, PBFC-based self-powered biosensors (PBFC-SPBs) have demonstrated the advantages of no need for external power supply, ease of sensing design, and simple instrument. , In particular, compared to BFC-based SPBs, the enzyme component in these biosensors is replaced by a photoanode, in which the electron donor could consume photogenerated holes and the remaining electrons would transfer to the cathode via the external circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-assisted biofuel cells (PBFCs) are a class of photoelectric conversation technology that uses the integration of photoelectrochemistry (PEC) 19 and biofuel cells (BFCs). 20−22 They have attracted extensive attention and have been widely applied in analysis and energy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, recent reports have demonstrated that the in situ generation of heterostructures by self-passivated Cs 3 Bi 2 Br 9 QDs with BiOBr could prominently improve the stability. 27 However, the application of the Bi-based perovskite in the field of PEC biosensing has rarely been exploited, 28 especially, the introduction of some synergistic effects is expected to improve the photoelectric performance. 29,30 Some studies have reported that traces of water treatment could encapsulate Cs 3 Bi 2 Br 9 QDs within the BiOBr matrix.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, recent reports have demonstrated that the in situ generation of heterostructures by self-passivated Cs 3 Bi 2 Br 9 QDs with BiOBr could prominently improve the stability . However, the application of the Bi-based perovskite in the field of PEC biosensing has rarely been exploited, especially, the introduction of some synergistic effects is expected to improve the photoelectric performance. , Some studies have reported that traces of water treatment could encapsulate Cs 3 Bi 2 Br 9 QDs within the BiOBr matrix. The water treatment process has been demonstrated to be an effective way to improve the stability and PL performance, although the inherent improvement mechanisms remain unclear in this field, which provide a unique perspective to explore strategies for Bi-based perovskite PEC sensing.…”
Section: Introductionmentioning
confidence: 99%